2016
DOI: 10.1111/eje.12212
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of dental students in Japanese national universities about studying abroad

Abstract: Overall, language ability and academic knowledge appeared to be the two strongest factors affecting dental students' consideration of studying abroad. Dental schools in Japan can use the findings of this study to improve their undergraduate exchange programs in such a way as to stimulate greater interest amongst their students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…First, there was a stronger emphasis on a group of students or study destination. For example, in recent years, the research on international students’ mental health showed a strong focus on the Chinese [ 80 , 81 , 82 , 83 ], Japanese [ 84 , 85 ], and medical international students [ 86 , 87 , 88 ]. Meanwhile, Australia has received more attention as a study destination [ 83 , 89 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, there was a stronger emphasis on a group of students or study destination. For example, in recent years, the research on international students’ mental health showed a strong focus on the Chinese [ 80 , 81 , 82 , 83 ], Japanese [ 84 , 85 ], and medical international students [ 86 , 87 , 88 ]. Meanwhile, Australia has received more attention as a study destination [ 83 , 89 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study was performed in accordance with the World Medical Association Declaration of Helsinki, and the experimental protocol and consent procedure were approved by the ethical committee of XXX University (Epd‐1097‐1) before starting the study. We used a questionnaire “An Attitude Survey on Studying Abroad” administered to second‐ through sixth‐year students ( n = 776) from three national university dental schools established in the same year and located in different areas (East, Central, West) within Japan (Oka, Ishida, Hong, & Nguyen, ). In the three schools, undergraduate dental students mainly study liberal arts in the first year, then they mainly study in the preclinical and undergraduate clinical program for around 5 years.…”
Section: Methodsmentioning
confidence: 99%
“…As the o cial language of international conferences, academic journals and websites, English brings challenges to students and health professionals from non-English-speaking countries. 1,2 With the increasing internationalization of health profession education in countries around the world, English education in professional areas has become increasingly important. 3 Studies have shown that in non-English-speaking countries such as Japan, competency and con dence in the English language could be one of the largest obstacles for stomatology students to study abroad.…”
Section: Introductionmentioning
confidence: 99%